Resolving the generation mechanisms and electrodynamical effects of Medium Scale Traveling Ionospheric Disturbances (MSTIDs) - Klenzing, Jeff; Zawdie, Kate; Astafyeva, Elvira; Belehaki, Anna; Burleigh, Meghan; Burrell, Angeline G.; Figueiredo, Cosme A. O. B.; Frissell, Nathaniel A.; Fu, Weizheng; Hickey, Dustin; Huba, Joe; Inchin, Pavel; et al. (Frontiers in Astronomy and Space Sciences, 2025)
The term “Medium-Scale Traveling Ionospheric Disturbances” is used to describe a number of different propagating phenomena in ionospheric plasma density with a scale size of hundreds of km. This includes multiple generation mechanisms, including ion-neutral collisions, plasma instabilities, and electromagnetic forcing. Observational limitations can impede characterization and identification of MSTID generation mechanisms. We discuss inconsistencies in the current terminology used to describe these and provide a set of recommendations for description and discussion.